KINERJA FINANSIAL BANK PERKREDITAN RAKYAT MILIK PEMERINTAH DAERAH DAN MILIK SWASTA DI PROVINSI RIAU - Afriyanto, Kamaliah, Zulbahridar (Fakultas Ekonomi Universitas Pasir Pengaraian, 2016)
This research aimed to analyze the differences in the financial performance of ruralbanks owned of local government with rural bank owned of private in terms of CAR, NPL,PPAP, ROA, ROA, CR, and LDR factors. Data analysis techniques in quantitative researchuses statistical analysis consisted of a descriptive statistical analysis and inferentialstatistical analysis. Descriptive statistical analysis was used to describe the characteristicsof the variables researched, while the inferential statistical analysis was used to see thedifference in financial performance of rural banks owned of local government and owned ofprivate by using a statistical test by the use of test model Mann-Whitney. Based on theresults of the research showed that the average ratio of CAR, PPAP, ROA, ROA, and CRbetween rural banks owned of local government with rural bank owned of private nodifference and financial performance both are in a healthy condition, while the averageratio of NPL in an equally unhealthy conditions. For average ratio LDR of rural bankowned of local government are in unhealthy conditions while the average ratio of LDR ofrural bank owned of private in unsanitary conditions. Overall, there was no difference infinancial performance between rural banks owned of local government with rural bankowned of private.